Pengembangan E-Modul Menggunakan Heyzine Flipbook pada Materi Interaksi Sosial di Lingkungan Sekolah dan Masyarakat untuk Meningkatkan Hasil Belajar Peserta Didik - Audi Octaviani; Nita Karmila; Fitri Siti Sundari (Mataram University, 2026)
Learning in elementary schools still uses teaching materials in the form of printed books so that students have difficulty understanding the material and learning outcomes are not optimal. Therefore, this study aims to develop an e-module using Heyzine flipbook on the material of social interaction in the school environment and the community, determine the feasibility of the product, and test its effectiveness on the learning outcomes of fourth-grade students at SDN Menteng, Bogor City. The research method uses Research and Development with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The research subjects consisted of validators, material experts, linguists, media experts, teachers, and 28 students of class IV-A. Data were collected through observation, interviews, validation questionnaires, response questionnaires, and pretest and posttest tests. The results of the validation recapitulation showed that material experts were 94%, linguists 97%, and media experts 86% with an average of 92.33% in the very feasible category. Student responses obtained 91% and teacher responses 100% in the very practical category. The product's effectiveness was demonstrated by an increase in the average score from 71.93 to 95.32, with an N-Gain of 0.87 and an N-Gain percentage of 86.53%, in the high and effective categories. Thus, the Heyzine flipbook e-module is feasible, practical, and effective for improving student learning outcomes.